Community norms for the Eating Disorder Examination Questionnaire (EDE-Q) among gender-expansive populations - Jason M. Nagata; Emilio J. Compte; Chloe J. Cattle; Annesa Flentje; Matthew R. Capriotti; Micah E. Lubensky; Stuart B. Murray; Juno Obedin-Maliver; Mitchell R. Lunn (Journal of Eating Disorders, 2020)
Abstract Purpose Gender-expansive individuals (i.e., those who identify outside of the binary system of man or woman) are a marginalized group that faces discrimination and have a high burden of mental health problems, but there is a paucity of research on eating disorders in this population. This study aimed to describe the community norms for the Eating Disorder Examination Questionnaire (EDE-Q) in gender-expansive populations. Methods The participants were 988 gender-expansive individuals (defined as neither exclusively cisgender nor binary transgender) from The PRIDE study, an existing longitudinal cohort study of health outcomes in sexual and gender minority people. Results We present the mean scores, standard deviations, and percentile ranks for the Global score and four subscale scores of the EDE-Q in this group as a whole and stratified by sex assigned at birth. Gender-expansive individuals reported any occurrence (≥1/28 days) of dietary restraint (23.0%), objective binge episodes (12.9%), excessive exercise (7.4%), self-induced vomiting (1.4%), or laxative misuse (1.2%). We found no statistically significant differences by sex assigned at birth. Compared to a prior study of transgender men and women, there were no significant differences in eating attitudes or disordered eating behaviors noted between gender-expansive individuals and transgender men. Transgender women reported higher Restraint and Shape Concern subscale scores compared to gender-expansive individuals. Compared to a prior study of presumed cisgender men 18–26 years, our age-matched gender-expansive sample had higher Eating, Weight, and Shape Concern subscales and Global Score, but reported a lower frequency of objective binge episodes and excessive exercise. Compared to a prior study of presumed cisgender women 18–25 years, our age-matched gender-expansive sample had a higher Shape Concern subscale score, a lower Restraint subscale score, and lower frequencies of self-induced vomiting, laxative misuse, and excessive exercise. Conclusions Gender-expansive individuals reported lower Restraint and Shape Concern scores than transgender women; higher Eating, Weight, and Shape Concern scores than presumed cisgender men; and lower Restraint but higher Shape Concern scores than presumed cisgender women. These norms can help clinicians in treating this population and interpreting the EDE-Q scores of their gender-expansive patients.